TRANSISI DEMOGRAFI DAN PEMBANGUNAN BERKELANJUTAN* - Siswanto Agus Wilopo (Populasi, 1995)
From a number of studies there are evidences of the existence of integration between "demography variables" and the development process. In this case it is important to understand that the population policies have been formulated for the continuity of development process, mainly by paying attention to the integration between people (inhabitants) and their environment. In this case, the government's policy is to stabilize economic development, distributing it evenly and maintain the environment in accordance with the global Population Action Program. The problems caused by changes related to the demographic transition can be considered the material for the future demographic policies.